2017
DOI: 10.1186/s12864-017-3670-1
|View full text |Cite
|
Sign up to set email alerts
|

Poplar stem transcriptome is massively remodelled in response to single or repeated mechanical stimuli

Abstract: BackgroundTrees experience mechanical stimuli -like wind- that trigger thigmomorphogenetic syndrome, leading to modifications of plant growth and wood quality. This syndrome affects tree productivity but is also believed to improve tree acclimation to chronic wind. Wind is particularly challenging for trees, because of their stature and perenniality. Climate change forecasts are predicting that the occurrence of high wind will worsen, making it increasingly vital to understand the mechanisms regulating thigmom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 57 publications
(71 reference statements)
5
59
0
Order By: Relevance
“…Jarin-1 had no effect on shoot elongation ( Figure S2b). 3.6 | Thigmomorphogenesis-related gene expression is altered in buds in response to leaf removal Previous studies in a diverse species have discovered transcriptional changes responsive to mechanical stimulation (Ishihara, Lee, & Borthakur, 2017;Lee et al, 2005;Pomiès, Decourteix, Franchel, Moulia, & Leblanc-Fournier, 2017). Sorghum homologs of Arabidopsis genes induced by touch (Lee et al, 2005) were identified in the set of bud genes differentially expressed in response to leaf removal.…”
Section: Aba and Ja Regulate Bud Growthmentioning
confidence: 99%
“…Jarin-1 had no effect on shoot elongation ( Figure S2b). 3.6 | Thigmomorphogenesis-related gene expression is altered in buds in response to leaf removal Previous studies in a diverse species have discovered transcriptional changes responsive to mechanical stimulation (Ishihara, Lee, & Borthakur, 2017;Lee et al, 2005;Pomiès, Decourteix, Franchel, Moulia, & Leblanc-Fournier, 2017). Sorghum homologs of Arabidopsis genes induced by touch (Lee et al, 2005) were identified in the set of bud genes differentially expressed in response to leaf removal.…”
Section: Aba and Ja Regulate Bud Growthmentioning
confidence: 99%
“…A single event of MS from exogenous water spray to Arabidopsis seedlings growing in artificial media or the bending of leaves from soil grown plants, has been reported to cause large-scale differential gene expression of 10 and 2.5% respectively, in naïve Arabidopsis tissues [9,10]. The majority of MS-responsive genes were implicated in cell wall modifications, hormone regulation, organelle, and calcium signalling, that collectively mediate stress acclimation responses in plants [9][10][11][12]. In the absence of MS, the expressions of most MS-responsive transcripts returned to their basal level of expression.…”
Section: Introductionmentioning
confidence: 99%
“…TW, developed on the upper side of angiosperms branches, is characterised by extremely low MFA values and this is often associated with upregulation of many of cytoskeleton component and secondary wall formation genes, including those listed previously [41,101,[104][105][106][108][109][110][111][112]. Accordingly, Li et al [113] found the same genes overexpressed in high stiffness wood in Pinus radiata, which also has lower MFA when compared to low stiffness wood.…”
Section: Molecular Control Of Mfamentioning
confidence: 97%